A Dynamic Approach to a Comparative Evaluation of Financial Performance of Sections and Sectors of the Polish Economy - Skoczylas, Wanda; Batóg, Barbara (Acta Universitatis Lodziensis. Folia Oeconomica, 2019)
Financial performance of companies and their groups is of major interest to all stakeholders. As a result, they assess categories such as profitability, financial liquidity, financial independence, and risk. Separate analyses carried out for each of those elements alone do not always deliver conclusive findings, which is where synthetic methods are helpful. A ranking based on the taxonomic measure of development is one of such methods. The aim of the paper is, firstly, to present opportunities for using a dynamic version of the taxonomic measure of development in a comparative and complex assessment of financial performance in PKD divisions (Polish Classification of Activity), and, secondly, to evaluate changes in this area in the years 2014–2016. The data used for developing the ranking were sourced from the joint publication of industry indicators by the Financial Analysis Commission at the Research Council of the Accountants Association in Poland and InfoCredit, and from the Statistics Poland.